2018
DOI: 10.1177/0266666918770712
|View full text |Cite
|
Sign up to set email alerts
|

Media coverage of climate change information by the Tanzania Guardian and Daily News in 2015

Abstract: The study examined the reportage of information on climate change in the Guardian and the Daily News, two leading broadsheet newspapers in Tanzania. Data were collected and analysed using the informetrics method. Content analysis was used to delineate themes. Quantitative data generated was analysed using Microsoft Office Excel Software 2007 to generate graphs and charts. In all, 338 articles from 728 newspaper issues from January to December 2015 were collected and analysed. Key findings indicate that climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…Journalists usually seek climate change information from conferences, universities, the internet, print, research institutions, experts, politicians and researchers (Han et al 2017; Elia, 2018; Science Africa, 2011). Their access to credible, current, relevant, timely and comprehensive information (Attfield and Dowell, 2002; Siyao and Sife, 2018) is crucial for climate change adaptation and sustainable development (Shanahan, 2011; Elia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Journalists usually seek climate change information from conferences, universities, the internet, print, research institutions, experts, politicians and researchers (Han et al 2017; Elia, 2018; Science Africa, 2011). Their access to credible, current, relevant, timely and comprehensive information (Attfield and Dowell, 2002; Siyao and Sife, 2018) is crucial for climate change adaptation and sustainable development (Shanahan, 2011; Elia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Internet websites can potentially enable newspaper journalists to access and share huge amounts of information on climate change from different sources, thus reducing the cost of searching for, gathering, and sharing current and relevant information (e.g. see Elia, 2019b; Harbinson et al, 2006; Hossain and Islam, 2012; Mahajan and Kumar, 2017). Interesting further discussions with upcountry newspaper journalists indicated that these journalists mostly used Internet services such as email to communicate their news to newsrooms, but did not mostly use Internet services as a search facility for climate change information.…”
Section: Resultsmentioning
confidence: 99%
“…There is also a scarcity of scientific literature on the challenges encountered by newspaper journalists when covering climate change information in Tanzania. The little literature that is available is mostly on the coverage of climate change information in Tanzanian newspapers and the challenges encountered by the general category of journalists when covering information in their media (Elia, 2019a, 2019b, 2019c; Siyao and Sife, 2018; Tairo, 2013). Knowledge of such sources helps the generators of climate change information to know the reliable and accessible channels through which they can direct this information for further dissemination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Tanzania, Ogessa and Sife (2017) reported that only 4.9% of agricultural articles were placed on the front pages of the newspapers that were published in the four daily newspapers in 5 years between 2010 and 2015. Elia (2018) observed a low trend of Tanzanian newspaper to publishing climate change information in front pages in two Tanzanian newspapers. Similarly, Nkya (2017) reported that developmental news affecting the lives of the average Tanzanian citizens hardly receive prominence in the news reported in the media of national status.…”
Section: Introductionmentioning
confidence: 98%
“…It has been repeatedly reported that newspapers attach inadequate priority in publishing developmental and scientific issues as compared to political and social issues (Bacon, 2013; Elia, 2018; Mudombi et al, 2014; Narayana and Kumar, 2009; Nkya, 2017; Ogessa and Sife, 2017; Okorie and Oyedepo, 2011; Tagbo, 2010). Bacon (2013) reported an overall inadequacy of publishing stories about climate change science prominently in the Australian newspapers.…”
Section: Introductionmentioning
confidence: 99%